Fructan biosynthesis gene expression upon cold acclimation in orchardgrass (Dactylis glomerata L.) - B. Shaun Bushman (Grassland Research, 2025)
Abstract Background Fructan content and flux in temperate forages can benefit the grasses through increased cold hardiness, increased drought tolerance, and improved forage quality. Orchardgrass (Dactylis glomerata L., or cocksfoot) produces relatively long and unbranched levan‐type fructans, but the genes involved in their biosynthesis are uncharacterized. Methods Through the evaluation of five orchardgrass cultivars and breeding lines that differ in their cold hardiness and freezing tolerance, we tested fructan and monosaccharide accumulation upon cold acclimation. The glycoside hydrolase‐32 (GH32) gene family members involved in fructan biosynthesis were identified and grouped with homologous genes from Triticum aestivum and Lolium perenne. Results In each of four GH32 gene families, there were specific genes with high transcript levels and no deletions in GH32 motifs. The candidate for sucrose:fructan 6‐fructosyltransferase (6‐SFT) exhibited the highest transcript levels of any GH32 gene in this study and was induced upon cold acclimation. Conversely, three invertase and two fructan exohydrolase genes, with roles in sucrose and fructan hydrolysis, had reduced transcript levels upon cold acclimation. Conclusions These data provide putative roles of GH32 genes in orchardgrass, and show that 6‐SFT, vacuolar invertase (VI), and fructan exohydrolases (FEH) genes play a role in fructan biosynthesis and metabolism for cold acclimation in orchardgrass.